Eyelid hook injury - a preventable domestic injury. - Omar, Nazri; Md. Salleh, Rafidah (Elsevier, 2009)
The aim of this report is to describe the presentation and management of eyelid injury resulting from the hook of a rubber string. A seven-year-old boy presented with pain of the right upper eyelid. A rubber string with metal hook ends, snatched his right eye from below. The hook pierced through his upper eyelid from the conjunctival surface and remained in situ. However, there was no globe laceration noted. Removal was performed by reverse-tracking of the hook through the wound. The wound was stitched with 6'0 Vicryl sutures. Healing was excellent with minimal scarring.